Australian Journal of Water Resources - Australian Journal of Water Resources (Taylor & Francis, 2026)
The Australasian Journal of Water Resources ( AJWR) is a multi-disciplinary regional journal dedicated to scholarship, professional practice and discussion on water resources planning, management and policy. Its primary geographic focus is on Australia, New Zealand and the Pacific Islands. Papers from outside this region will also be welcomed if they contribute to an understanding of water resources issues in the region. Such contributions could be due to innovations applicable to the Australasian water community, or where clear linkages between studies in other parts of the world are linked to important issues or water planning, management, development and policy challenges in Australasia. These could include papers on global issues where Australasian impacts are clearly identified.
FI 0.68
Q2
Keywords: Engineering; Computing & Technology; Recursos hídricos; Acuerdos transformativos; Transformative agreements; Hidrología (aguas superficiales, aguas subterráneas, inundaciones, sequías); Planificación del agua; Desarrollo del agua; Derecho del agua; Economía del agua; Psicología y procesos de toma de decisiones en la gestión del agua